Modernity and re-enchantment : religion in post-revolutionary Vietnam - Vietnam Update Conference (2005 : Canberra, Australia); Taylor, Philip, 1962-; Institute of Southeast Asian Studies (Singapore : Institute of Southeast Asian Studies, 2007)
99